If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -1)(3x + 4) = 2 Reorder the terms: (-1 + 2x)(3x + 4) = 2 Reorder the terms: (-1 + 2x)(4 + 3x) = 2 Multiply (-1 + 2x) * (4 + 3x) (-1(4 + 3x) + 2x * (4 + 3x)) = 2 ((4 * -1 + 3x * -1) + 2x * (4 + 3x)) = 2 ((-4 + -3x) + 2x * (4 + 3x)) = 2 (-4 + -3x + (4 * 2x + 3x * 2x)) = 2 (-4 + -3x + (8x + 6x2)) = 2 Combine like terms: -3x + 8x = 5x (-4 + 5x + 6x2) = 2 Solving -4 + 5x + 6x2 = 2 Solving for variable 'x'. Reorder the terms: -4 + -2 + 5x + 6x2 = 2 + -2 Combine like terms: -4 + -2 = -6 -6 + 5x + 6x2 = 2 + -2 Combine like terms: 2 + -2 = 0 -6 + 5x + 6x2 = 0 Factor a trinomial. (-3 + -2x)(2 + -3x) = 0Subproblem 1
Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5Subproblem 2
Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667Solution
x = {-1.5, 0.6666666667}
| 59-7x=2x+18 | | 3y+12=3y | | 9x-2(4x+5)=32 | | x+x+2+x+4=147 | | -0.6=-3 | | =3a+7b+4+7a | | -6=x-(3-4x) | | 3x-8=-23 | | 3x+23=11x-49 | | -6a+11=-22 | | 8h-9=8h | | 3(-14+2)=13 | | 4x-30=2x+20 | | =8x+y+4x+2y | | 8s+6=54 | | -5,3/4=-2,1/2(m) | | -4.8f+9=-5 | | 3x+5=2x-2 | | 3p-200=200-2p | | x+50x=220 | | 4(2n+9)+15n=30n-6 | | x-143+512=745 | | (x+6)(x-9)=-14 | | 4x=3x-1+5+2x | | =x+3y+12+5y | | 2/3-9=6-2/3 | | -2p+(8p-6)=-18 | | 5(4Z-1)-3(2+7)=14(Z+1) | | =2x+9y+6x | | x^2-21x+100=-3x | | 7x=9+8x | | 12-3f=5f+1 |